2013
DOI: 10.1186/1742-2094-10-152
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome induction in Rasmussen’s encephalitis: cortical and associated white matter pathogenesis

Abstract: BackgroundRasmussen’s encephalitis (RE) is an inflammatory encephalopathy of unknown cause defined by seizures with progressive neurological disabilities. Herein, the pathogenesis of RE was investigated focusing on inflammasome activation in the brain.MethodsPatients with RE at the University of Alberta, Edmonton, AB, Canada, were identified and analyzed by neuroimaging, neuropsychological, molecular, and pathological tools. Primary human microglia, astrocytes, and neurons were examined using RT-PCR, enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 29 publications
4
61
0
Order By: Relevance
“…Elevated IL-1β and IL-1R1 have also been observed in brain tissue from patients with temporal lobe epilepsy and hippocampal sclerosis, and elevated IL-1β has been reported in cerebrospinal fluid (CSF) from children with febrile seizures [28,29]. In addition to increased IL-1 expression in patients with temporal lobe epilepsy, increases in IL-1β and inflammasome components have also been observed in other seizure disorders such as Rasmussen's encephalitis [30] and malformations of cortical development [31].…”
Section: Il-1β and Hmgb1 Expression In Seizuresmentioning
confidence: 85%
“…Elevated IL-1β and IL-1R1 have also been observed in brain tissue from patients with temporal lobe epilepsy and hippocampal sclerosis, and elevated IL-1β has been reported in cerebrospinal fluid (CSF) from children with febrile seizures [28,29]. In addition to increased IL-1 expression in patients with temporal lobe epilepsy, increases in IL-1β and inflammasome components have also been observed in other seizure disorders such as Rasmussen's encephalitis [30] and malformations of cortical development [31].…”
Section: Il-1β and Hmgb1 Expression In Seizuresmentioning
confidence: 85%
“…Microglia were lost in FDUtreated cultures. Another difference is that Ramaswamy et al, 37 cultured their cells in 10% serum whereas we used 5% decomplemented serum. It has been reported that complement can activate the NLRP3 inflammasome in dendritic cells 46 and a similar mechanism in primary human neurons would explain the difference between our results.…”
Section: Discussionmentioning
confidence: 96%
“…23,24,44 Furthermore, spatial memory deficits induced in familial AD-associated mutant APP/ PS1 mice were abrogated on a null NLRP3 background. 45 Although this differential expression could be species dependent, others have observed NLRP3 in human neuronal cultures, 37 suggesting that culture conditions may alter the levels of inflammasome receptors in primary human neuronal cell types. Cells respond to their extracellular environment so the conditions of cell culture could strongly influence the expression of certain genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations